Variability and Feedbacks in the Atlantic Freshwater Budget of CMIP5 Models With Reference to Atlantic Meridional Overturning Circulation Stability - Haines, Keith; Ferreira, David; Mignac, Davi (Frontiers in Marine Science, 2022)
It has been suggested that freshwater transports by the Atlantic Meridional Overturning Circulation (AMOC) in the south Atlantic may be a useful metric for determining the stability of the AMOC because it can lead to feedbacks onto North Atlantic salinities and hence deep water formation. In this paper we investigate feedbacks between south Atlantic Freshwater transports, Freshwater content and AMOC strength across different Atlantic latitudes, and at different timescales in centennial runs of 10 CMIP5 climate models, with both northward and southward AMOC freshwater transports in the south Atlantic. In all models, salinity variations are more important than AMOC variations in determining south Atlantic freshwater transports, especially on longer timescales >10 years. Only in the north Atlantic do AMOC variations become important in changing the meridional freshwater transports, which might then lead to feedbacks with stability implications. Closed budgets of Freshwater content show that south Atlantic transports only influence local freshwater budgets (within ~10 latitude) and that variations in horizontal transports by the south Atlantic gyre always dominate the overturning transports in all models and timescales. These results suggest that south Atlantic freshwater transports by the AMOC is highly unlikely to be a useful metric is determining AMOC stability as meridional freshwater transports are much less meridionally coherent than the AMOC circulation itself in all 10 CMIP5 models studied.